PERAN MODERASI PROFITABILITAS PADA PENGARUH CORPORATE SOCIAL RESPONSIBILITY DAN PERTUMBUHAN PENJUALAN TERHADAP NILAI PERUSAHAAN [THE MODERATING ROLE OF PROFITABILITY ON THE INFLUENCE OF CORPORATE SOCIAL RESPONSIBILITY AND SALES GROWTH ON COMPANY VALUE] - Wahyuni, Endah Sri (Perkumpulan Ahli Bimbingan dan Konseling Islam Indonesia, 2024)
This study aims to determine the effect of corporate social responsibility and sales growth on company value, as well as to analyze profitability able to strengthen or weaken the relationship between corporate social responsibility and sales growth on company value. The population in this study is processed food and beverage sub-sector companies listed on the Indonesia Stock Exchange in the financial statements for the 2018-2022 period. The sampling technique in this study used the purposive sampling method and obtained samples from 19 companies. The analysis techniques used are multiple linear regression analysis and Moderated Regression Analysis (MRA) using SPSS software version 22.0. The results of this study show that corporate social responsibility has a negative and significant influence on company value, sales growth has no influence and is significant on company value, profitability is able to strengthen the influence of corporate social responsibility relationship on company value, and profitability does not moderate the influence of sales growth relationship on company value.